OPTIMIZATION OF OOMYCETES PUFA (POLYUNSATURATED FATTY ACID) PRODUCTION BY SUBMERGED FERMENTATION METHOD USING PALM OIL SUGAR MEDIA - Hanifah, Syadza
Microbial lipid or Single Cell Oil (SCO) is an alternative to omega-3 and omega-6 polyunsaturated fatty acids (PUFA) as a dietary supplement to prevent various inflammatory and cardiovascular diseases. SCO has many advantages including rapid cultivation, not affected by climate, and does not require large areas of land. However, industrial-scale SCO production is often constrained by high production costs. The cost of carbon source is a major factor contributing to the cost of about 60-80% of the total production cost. Therefore, the utilization of cheap renewable carbon sources is necessary to make SCO production economically viable. Palm sap is an alternative carbon source that is rich in macronutrients and micronutrients, such as sugars (glucose, fructose, sucrose, arabinose, and galactose), amino acids (serine, glutamic acid, and alanine), organic acids (malic acid, maleic acid, citric acid), minerals and vitamins (vitamin B and vitamin C). Oil palm sap is abundant in Indonesia. Oomycetes is one of the microorganisms capable of producing PUFA. However, Oomycetes as a producer of PUFA is still rarely done in Indonesia. Therefore, this study aims to isolate Oomycetes from nature as PUFA-producing oleaginous microorganisms, characterize and identify oleaginous Oomycetes isolate, and optimize lipid production of oleaginous Oomycetes isolate using palm sugar as a fermentation medium. In this study, isolation was carried out starting with the feeding of isolate from fish ponds in the Bandung City area. The isolate obtained were then subjected to macroscopic and microscopic morphological characterization using a microscope. Oomycetes isolate were then identified genomically. PUFA accumulation ability of Oomycetes isolate was tested qualitatively with TTC (trifenyltetrazolium chloride) test and confirmed quantitatively with GC-MS. Optimization of lipid production of Oomycetes isolate began with the creation of radial curves and adaptation curves to determine the age of the inoculum. Parameters optimized include palm sugar concentration with variations of 2,5%, 5%, 7,5%, and 10% (w/v), pH with variations of 5, 6, 7 and 8 and inoculum concentration with variations of 10%, 20%, 30%, and 40% (v/v). In each treatment, dry biomass, pH and lipid content were measured every 24 hours for 7 days. Lipid content was measured by Folch method using chloroform:methanol 2:1 with solvent:biomass ratio of 20:1 v/w. The results showed that the isolated isolate was Achlya sp. and confirmed to accumulate PUFA. Based on the results of the radial curve and adaptation curve, the inoculum age was obtained at 72 hours. Based on One-way ANOVA statistical test and fisher's further test, the optimum palm sugar concentration was obtained at a variation of 7,5% (w/v) with biomass 1.571 ± 60 mg/L, lipid 285 ± 4,25 mg/L, and lipid content of 18,16 ± 0,91% (w/w), optimum pH at pH 5 with biomass 1.571±60 mg/L, lipid 285±4,25 mg/L, and lipid content of 18,16±0,91% (w/w), and optimum concentration at 40% (v/v) with biomass 4.370±120 mg/L, lipid 882±25,45 mg/l, and lipid content 20,20±0,03% (w/w). Therefore, the brown sugar concentration of 7,5% (w/v), pH 5 with 40% (v/v) inoculum was chosen as the optimum variation which was then produced on a large scale to analyze the fatty acid content using GC-MS and it was found that Achlya sp. can produce PUFA omega-6 0,50±0,01% and omega-3 0,54±0,01%.